The economics of resource rich economies - Ploeg, Frederick van der 1956- (Edward Elgar Pub. Ltd, 2015)
The Economics of Resource Rich Economies discusses the problems and benefits of economies rich in natural resources. After a brief look at some historical aspects, it explores the concept known as the 'Dutch Disease' and offers empirical and theoretical insights into the effects of rich natural resources on economic growth. It investigates the political economy of natural resources, issues of conflict and natural resources and a variety of policies and strategies for managing the revenue from natural resources
Keywords: Rohstoffwirtschaft; Natural resources; Electronic books; Aufsatzsammlung